Genetic and physiological insights into the diazotrophic activity of a non-cyanobacterial marine diazotroph - Joublin-Delavat, Aurélie; Touahri, Katia; Crétin, Pauline; Morot, Amandine; Rodrigues, Sophie; Jesus, Bruno; Trigodet, Florian; Delavat, François (bioRxiv, 2022)
Nitrogen (N2) fixation, or diazotrophy, supports a large part of primary production in oceans. Culture-independent approaches highlighted the presence in abundance of marine non-cyanobacterial diazotrophs (NCD) but their ecophysiology remains elusive, mostly because of the low number of isolated NCD and because of the lack of available genetic tools for these isolates. Here, a dual genetic and functional approach allowed unveiling the ecophysiology of a marine NCD affiliated to the species Vibrio diazotrophicus. Physiological characterization of the first marine NCD mutant obtained so far was performed using a soft-gellan assay, demonstrating that a ΔnifH mutant in not able to grow in nitrogen-deprived media. Furthermore, we demonstrated that V. diazotrophicus produces a thick biofilm under diazotrophic conditions, suggesting biofilm production as an adaptive response of this NCD to cope with the inhibition of nitrogen-fixation by molecular oxygen. Finally, the genomic signature of V. diazotrophicus is essentially absent from metagenomic data of Tara Ocean expeditions, despite having been isolated from various marine environments. We think that the genetically tractable V. diazotrophicus strain used in this study may serve as an ideal model to study the ecophysiology of these overlooked procaryotic group.